2017
DOI: 10.1021/acsomega.6b00211
|View full text |Cite
|
Sign up to set email alerts
|

Azadioxatriangulenium and Diazaoxatriangulenium: Quantum Yields and Fundamental Photophysical Properties

Abstract: Over the last decade, we have investigated and exploited the photophysical properties of triangulenium dyes. Azadioxatriangulenium (ADOTA) and diazaoxatriangulenium (DAOTA), in particular, have features that make them useful in various fluorescence-based technologies (e.g., bioimaging). Through our work with ADOTA and DAOTA, we became aware that the reported fluorescence quantum yields (phi(fl)) for these dyes are lower than their actual values. We thus set out to further investigate the fundamental structure-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 93 publications
6
54
0
Order By: Relevance
“…First, the results concerning the ADOTA derivatives will be discussed. The absorption and emission spectra of 3 a – 3 cPF 6 measured at pH 2 (Figure A and Table ) are comparable to those measured for similar ADOTA derivatives and the methyl reference compound 3 d ,. The integrated fluorescence intensities (I f ) converge towards zero, as the pH values approaches the basic pH region (Figure A).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…First, the results concerning the ADOTA derivatives will be discussed. The absorption and emission spectra of 3 a – 3 cPF 6 measured at pH 2 (Figure A and Table ) are comparable to those measured for similar ADOTA derivatives and the methyl reference compound 3 d ,. The integrated fluorescence intensities (I f ) converge towards zero, as the pH values approaches the basic pH region (Figure A).…”
Section: Resultssupporting
confidence: 75%
“…As previously reported the nature of the groups bound to the nitrogen bridges in ADOTA and DAOTA has negligible effects on their absorption and emission spectra . This is also found to be the case for the phenol substituted derivatives where shifts of less than 3 nm are observed when comparing to simple methyl derivatives of ADOTA ( 3 d ) and DAOTA ( 5 d ) shown in Figure . Spectral data are compiled in Table .…”
Section: Resultsmentioning
confidence: 75%
“…We have recently shown that the aza/oxa-triangulenium dyes; ADOTA + and DAOTA + ( Chart 1 ) have remarkable low rates of non-radiative deactivation and low susceptibility to quenching by oxygen, 31 which explains how these organic dyes with fluorescence peaks in the 550 nm–600 nm range, can display unusually long fluorescence lifetimes, close to 20 ns, and high quantum yields ( Φ f ≈ 0.7–0.8).…”
Section: Introductionmentioning
confidence: 99%
“… 44 51 While DMQA + displays long fluorescence lifetime in non-polar solvents it display faster non-radiative deactivation than the planer aza/oxa-triangulenium dyes and is practically non-fluorescent in aqueous solutions. 31 , 42 …”
Section: Introductionmentioning
confidence: 99%
“…[17,18] There is agrowing literature predicting the chemistry of 2 [19][20][21][22] and avariety of heterocyclic versions are known. [23][24][25][26][27][28][29][30] In spite of much effort in this field, the parent substance 2,c ommonly known as triangulene or Clarsh ydrocarbon, was only recently prepared and observed as single molecules by scanning probe microscopy. [31] Similar experiments describing the molecularscale preparation of higher homologues 3 and 4 by surfaceassisted dehydrogenation of suitable precursors have been reported very recently.…”
mentioning
confidence: 99%